Unlocking urban transportation carbon reduction potential: a dynamic evaluation of public transit adoption in response to carbon-centric policies - Peng, Ran; Ding, Keyuan; Liu, Xueliang; Yao, Keyu; Zhou, Xu; Zhang, Wei (Frontiers in Environmental Science, 2025)
IntroductionThe transition to carbon-centric urban policies requires innovative strategies to reduce transportation-related emissions. One such strategy is to shift travelers from high-carbon to low-carbon modes of transportation, a potential that has not been thoroughly quantified in urban planning frameworks.MethodsThis study introduces the concept of urban transportation carbon reduction potential, defined as the share of travelers who could feasibly switch to low-carbon modes under optimized public transit conditions. A dynamic evaluation model was developed, integrating key factors such as connection, detour, and transfer barriers that influence residents’ public transit adoption. The model was applied to cross-river travel in Wuhan, China, using 10,327 Origin-Destination (OD) survey data points collected between 2023 and 2024. Multiple optimization scenarios were simulated to assess responses to transit improvements.ResultsThe analysis revealed three distinct zones of carbon reduction potential: stable, unlocking, and re-stable. Particularly, the unlocking zone exhibited substantial carbon reduction effects when targeted public transit improvements were implemented. Key thresholds were identified where small enhancements in transit connectivity led to sharp increases in low-carbon travel adoption.DiscussionThis study presents a novel optimization model for urban transit planning, which explicitly incorporates natural environmental constraints and provides quantitative decision support for achieving SDG11 targets on sustainable cities and communities. It offers valuable insights for cities within the Yangtze River Economic Belt, aiding strategic investment in public transit to enhance low-carbon mobility.